The role of nonfinancial factors in the Congressional Budget Office’s health insurance coverage projections - Nianyi Hong; Ben Hopkins (Proceedings of the National Academy of Sciences, 2026)
Nonfinancial factors play an important role in people’s coverage decisions as premiums, cost sharing, and other factors that determine the financial value of health insurance cannot fully explain patterns in take-up rates. The Congressional Budget Office (CBO) is tasked with estimating the budgetary and coverage effects of policy and economic changes that affect health insurance markets, which includes considering the interactions between nonfinancial factors and policy design. The agency groups the nonfinancial factors it considers into three categories: ease of enrollment, awareness, and attitudes. Many recent policies have affected nonfinancial factors related to the take-up of Medicaid and marketplace insurance, such as the introduction of work requirements for Medicaid and access to zero-premium marketplace plans. This article explains how nonfinancial factors are handled and incorporated into CBO’s baseline health insurance projections and cost estimates, highlights the recent literature on the effect of these nonfinancial factors on insurance take-up decisions, and suggests future areas of research.